2020
DOI: 10.3389/fneur.2020.604612
|View full text |Cite
|
Sign up to set email alerts
|

Adult Sellar Region Atypical Teratoid/Rhabdoid Tumor: A Retrospective Study and Literature Review

Abstract: Background: Adult sellar region atypical teratoid/rhabdoid tumor (AT/RT) is a rare lesion. We aimed to elucidate clinical, radiologic, and pathological characteristics, treatment strategies, and outcomes of this disease.Methods: Five adult sellar AT/RT patients were retrospectively analyzed between January 2015 and December 2018. In addition, we performed a review of the reported data on adult sellar AT/RT.Results: Patients (n = 5) were female with a median age of 50 years. The mean duration of symptoms, of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…On the base of a literature review, we found 50 cases of ATRTs reported before (12,(15)(16)(17)(18)(19)(20); we have considered Articles that describe primitive sellar tumor cases in adults and were resulted ATRT with loss of INI, from 2000 to 2021 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the base of a literature review, we found 50 cases of ATRTs reported before (12,(15)(16)(17)(18)(19)(20); we have considered Articles that describe primitive sellar tumor cases in adults and were resulted ATRT with loss of INI, from 2000 to 2021 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, most adult AT/RTs found to belong to the ATRT‐MYC subgroup and further clinical and molecular heterogeneity in ATRT‐MYC may be revealed. 39 , 40 Using both in vitro and in vivo data, Alimova et al. 41 showed that the c‐MYC oncogene is a critical regulator of malignant behavior in SMARCB1‐deficient AT/RTs.…”
Section: Molecular Pathogenesis Of At/rtsmentioning
confidence: 99%
“…The median age is significantly higher among patients with ATRT‐MYC than among patients with the other subtypes of AT/RTs. Besides, most adult AT/RTs found to belong to the ATRT‐MYC subgroup and further clinical and molecular heterogeneity in ATRT‐MYC may be revealed 39,40 . Using both in vitro and in vivo data, Alimova et al 41 .…”
Section: Molecular Pathogenesis Of At/rtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, there are around 50 cases reported of adults; the average age was 36.69 (SD = 15.19) years with a range from 18 to 59 years [ 4 ]. Thirty-nine of these cases are sellar AT/RT in adults to date [ 5 ]. AT/RT can occur anywhere in CNS.…”
Section: Introductionmentioning
confidence: 99%